People with larger social networks are better at predicting what someone will say but not how they will say it. Issue 1 (2nd January 2019) - Lev-Ari, Shiri
ABSTRACT: Prediction of upcoming words facilitates language processing. Individual differences in social experience, however, might influence prediction ability by influencing input variability and representativeness. This paper explores how individual differences in social network size influence prediction and how this influence differs across linguistic levels. In Experiment 1, participants predicted likely sentence completions from several plausible endings differing in meaning or only form (e.g. work vs. job ). In Experiment 2, participants' pupil size was measured as they listened to sentences whose ending was the dominant one or deviated from it in either meaning or form. Both experiments show that people with larger social networks are better at predicting upcoming meanings but not the form they would take. The results thus show that people with different social experience process language differently, and shed light on how social dynamics interact with the structure of the linguistic level to influence learning of linguistic patterns.